A gut microbiota score predicting acute graft‐versus‐host disease following myeloablative allogeneic hematopoietic stem cell transplantation. Issue 4 (12th December 2019) - Han, Lijie; Zhao, Ke; Li, Yuanyuan; Han, Haohao; Zhou, Lizhi; Ma, Ping; Fan, Zhiping; Sun, Hui; Jin, Hua; Jiang, Zhongxing; Liu, Qifa; Peng, Jie
Abstract : Although studies have reported that intestinal microbiota are associated with acute graft‐versus‐host disease (aGVHD), they lacked a satisfactory method for predicting aGVHD. We collected stool and blood samples at day 15 posttransplant from 150 patients from two centers who underwent myeloablative conditioning allogeneic hematopoietic stem cell transplantation (allo‐HSCT). Stool microbiota were detected by 16S ribosomal RNA gene sequencing; inflammatory factors and T lymphocytes were detected by multiplex immunoassays and flow cytometry, respectively. A gut microbiota score (GMS) from a LASSO (least absolute shrinkage and selection operator) model was developed and validated to predict aGVHD. In the discovery cohort, the GMS could predict II‐IV aGVHD (area under the receiver operating characteristic [ROC] curve [AUC] = 0.904, P  <   .0001). Furthermore, the validation model was consistent with the discovery set (AUC = 0.887, P  <   .0001). Regulatory T/T‐helper 17 (Treg/Th17) cells ratio in the low GMS subgroup was higher compared with the high GMS ( P  =   .012), and the validation set is consistent with the discovery set ( P  =   .003). In addition, high cytokine levels were associated with high GMS. In conclusion, the GMS at neutrophil engraftment could predict aGVHD, and it was a potential and novel method. The GMS was associated with the inflammatory factor and Treg/Th17 balance. Abstract : Gut microbiota models could predict acute graft‐versus‐host disease after allogeneic transplantation.